Question

given a set of functional dependencies

given a set of functional dependencies


F = {AB → C, C → B}, above the relational scheme R (A, B, C).


Prove that {AB → AC, AB → BC, AC → B, AC → AB} F +


7 0
Add a comment Improve this question Transcribed image text
✔ Recommended Answer
Answer #1

Solution:

Given,

=>Set of functional dependency F = {AB -> C, C -> B}

=>Relation = R(A, B, C)

To prove: F+ = {AB -> AC, AB -> BC, AC -> B, AC -> AB}

Explanation:

Deriving AB -> AC:

=>(AB)+ = ABC using functional dependency {AB -> C, C -> B} hence we can write AB -> AC

Deriving AB -> BC:

=>(AB)+ = ABC using functional dependency {AB -> C, C -> B} hence we can write AB -> BC

Deriving AC -> B:

=>(AC)+ = ABC using functional dependency {AB -> C, C -> B} hence we can write AC -> B

Deriving AC -> AB:

=>(AC)+ = ABC using functional dependency {AB -> C, C -> B} hence we can write AC -> AB.

=>As we can see that we can cover all the functional dependency of the F+ set using attribute closure; hence F+ set is correct.

=>Hence based on the above statements, we have proved our result.


answered by: codegates
Add a comment
Know the answer?
Add Answer to:
given a set of functional dependencies
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Similar Homework Help Questions
ADVERTISEMENT
Free Homework Help App
Download From Google Play
Scan Your Homework
to Get Instant Free Answers
Need Online Homework Help?
Ask a Question
Get Answers For Free
Most questions answered within 3 hours.
ADVERTISEMENT
ADVERTISEMENT